Peningkatan Kapasitas dan Manajemen Agroeduwisata Desa Batulaya dengan Teknologi Hidroponik dan Vertikal Garden Berbahan Sampah Plastik - Nurdin, Rizaldi; Ariandi; Haloho, Ruth Dameria; Masniawati, Andi; Muis, Nurmuliayanti; Manguntungi, Baso (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to enhance agro-edutourism management in Batulaya Village through training on hydroponic and vertical garden technology, utilizing plastic waste as a planting medium. The agro-edutourism in this village has great potential but faces challenges in managing limited land and high levels of plastic waste. The training program involved 65 participants, including local farmers, village youth, and agro-edutourism managers. A qualitative method was used to collect data through questionnaires and observations, which were then analyzed using thematic analysis. The results show that the training successfully improved participants' knowledge and skills in applying hydroponic and vertical garden technology. A total of 85% of participants were able to understand the basic concepts of the technology, and 70% could utilize plastic waste as a planting medium. The activity concludes that training and improving agro-edutourism management based on hydroponics and vertical gardens in Batulaya Village not only succeeded in enhancing the community's technical capacity but also provided innovative solutions to environmental issues. However, challenges in accessing resources and technology need to be addressed to ensure the sustainability of this program.